Menurunkan Prilaku Membolos Dengan Layanan Konseling Individu Melalui Teknik Latihan Asertif Pada Siswa Kelas XI TKJ 2 SMK Raden Paku Wringinanom - Trisnawati, Ida (Universitas Nusantara PGRI Kediri, 2020)
Learning activities can be carried out if all components are met, namely teachers and students. In this modern era, truant behavior still occurs, especially students who do not have a stand, only join friends to skip class. The purpose of this classroom action research is the extent to which truancy behavior can be reduced with individual counseling through assertive training techniques to refuse invitations to truancy friends. The research subjects were students of class XI TKJ 2 SMK Raden Paku Wringinom for the 2020/2021 school year. The methods used in collecting data were questionnaires, interviews, and observations. The results obtained in the first cycle were still low, namely 55% of the success indicator, while the second cycle experienced a success rate of 87.5%. So it can be concluded that with assertive training students are firm in rejecting an invitation to truancy.